Surface investigation of chitosan film with fatty acid monolayers - El-hefian, E.A.; Misran, M.; Yahaya, A.H. (2009)
The surface pressure-molecular area (pi-A) isotherm curves of two fatty acids of different chain lengths, i.e. stearic (C(18)) and arachidic (C(20)) acids, were obtained by using Langmuir-Blodgett (LB) technique. Results showed clear isotherm plots with limiting mean molecular area around 21 angstrom(2) for both acids. However, the monolayer was found to collapse at higher than 33 mN m(-1) and 21 mN m(-1) for stearic acid and arachidic acid respectively. The effect of Langmuir-Blodgett monolayers of the acids was investigated by atomic force microscopy (AFM). Chitosan film, before and after dipping in water, was also studied by means of AFM so that it could be used for comparison. It was found that the surface of chitosan was more homogeneous and smoother after dipping in water. In addition, more homogeneous surfaces were achieved after transferring a layer of the fatty acid onto the substrate.